Climate change vulnerability of cetaceans in Macaronesia: Insights from a trait-based assessment - Sousa, A. (2021)
Over the last decades global warming has caused an increase in ocean temperature, acidification and oxygen loss which has led to changes in nutrient cycling and primary production affecting marine species at multiple trophic levels. While knowledge about the impacts of climate change in cetacean's species is still scarce, practitioners and policymakers need information about the species at risk to guide the implementation of conservation measures. To assess cetacean's vulnerability to climate change in the biogeographic region of Macaronesia, we adapted the Marine Mammal Climate Vulnerability Assessment (MMCVA) method and applied it to 21 species management units using an expert elicitation approach. Results showed that over half (62%) of the units assessed presented Very High (5 units) or High (8 units) vulnerability scores. Very High vulnerability scores were found in archipelago associated units of short-finned pilot whales (Globicephala macrorhynchus) and common bottlenose dolphins (Tursiops truncatus), namely in the Canary Islands and Madeira, as well as Risso's dolphins (Grampus griseus) in the Canary Islands. Overall, certainty scores ranged from Very High to Moderate for 67% of units. Over 50% of units showed a high potential for distribution, abundance and phenology changes as a response to climate change. With this study we target current and future information needs of conservation managers in the region, and guide research and monitoring efforts, while contributing to the improvement and validation of trait-based vulnerability approaches under a changing climate.